Effect of Feeding of Mulethi (Glycyrrhiza glabra) on Growth Performance and Nutrient Retention in Broiler Chicken - Nimje, Prapti; Sharma, Tribhuwan; Dhuria, R. K.; Kumari, Nirmala (Indian Journal of Animal Nutrition, 2017)
A total of 150, day old broiler chicken were randomly distributed into 5 treatments with two replicates having fifteen chicks in each replicate to evaluate the effect of supplementation of varying levels of mulethi (Glycyrrhiza glabra) on performance of broiler chicken.. The birds in treatment T1 were fed on basal diet while in treatments T2, T3, T4, T5, the basal diet was supplemented with 0.25, 0.5, 1.0 and 1.5% of mulethi reet powder, respectively. The feed intake was similar in different treatments. The weight gain was higher (P<0.05) in treatment T2 with better FCR. No significant difference was observed on performance index. The DM digestibility, nitrogen balance, dressed and eviscerated yield were found to be similar in all the groups. Therefore, inclusion of mulethi at 0.25% level in the ration improved body weight gain and feed conversion efficiency without affecting the feed intake in broiler chicken. Beyond this level of supplementation, there was no further improvement.